A multi-input energy harvesting system with independent energy harvesting block and power management block - Eun Jeong Yun; Hyeon Joong Kim; Chong Gun Yu (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
In the conventional approach widely used for multi-input energy harvesting (MIEH), energy harvesting, energy combining, and power conversion are performed integrally in an inductor sharing block through time multiplexing operations, which is not suitable for hot-pluggable systems. In the MIEH system proposed in this paper, an energy harvesting block (EHB) and a power management block (PMB) are independent of each other to increase the modularity of the system. Therefore, the EHB can be optimized to extract maximum power from energy sources, and the PMB can be focused on combining input energies and converting power effectively. This paper mainly focuses on the design and implementation of the EHB. For light, vibration, and thermal energy, the measured peak power efficiencies of the EHB implemented using a 0.35 μm CMOS process are 95.2%, 92.5%, and 95.5%, respectively. To confirm the functionality and effectiveness of the proposed MIEH system, a PMB composed of simple charge pump circuits and a power management unit has also been implemented and verified with the designed EHB.